2000
DOI: 10.4141/p99-062
|View full text |Cite
|
Sign up to set email alerts
|

Residues of glyphosate and its metabolite AMPA in canola seed following preharvest applications

Abstract: . 2000. Residues of glyphosate and its metabolite AMPA in canola seed following preharvest applications. Can. J. Plant Sci. 80: [425][426][427][428][429][430][431]. Residue data for glyphosate and its major metabolite aminomethylphosphonic acid (AMPA) in canola seed following preharvest application of glyphosate were lacking when this 2-yr study was initiated. Residues of glyphosate and AMPA were measured in the seed of canola (Brassica rapa L.) at maturity following preharvest application at rates of 0.45, 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 13 publications
1
18
0
Order By: Relevance
“…up to approximately 7% in seed or straw of barley. The levels of AMPA by and large followed the same pattern as those of glyphosate with regard to their dependency on application rates, stage of application and other environmental factors 60–63. These authors also mentioned that, in several different crops investigated in other studies, such as strawberry, no formation of AMPA had been observed.…”
Section: Herbicide‐resistant Cropsmentioning
confidence: 56%
“…up to approximately 7% in seed or straw of barley. The levels of AMPA by and large followed the same pattern as those of glyphosate with regard to their dependency on application rates, stage of application and other environmental factors 60–63. These authors also mentioned that, in several different crops investigated in other studies, such as strawberry, no formation of AMPA had been observed.…”
Section: Herbicide‐resistant Cropsmentioning
confidence: 56%
“…Samples were milled, extracted with aqueous HCl solution and cleaned up on an anion exchange resin. The purified extract was analysed by HPLC using fluorescence detection following post-column ophthalaldehyde derivatization (Cessna et al, 2000).…”
Section: Herbicide Residues Determined In Food and Food Products By Hmentioning
confidence: 99%
“…Because 5‐enolpyruvylshikimate‐3‐phosphate synthase is an enzyme present only in plants and some bacteria but not in vertebrates, glyphosate was initially considered nontoxic (Williams, Watson, & DeSesso, ), with an estimated lethal dose (LD 50 ) higher than 5000 mg/kg (EPA, US, ; Mensink & Janssen, ). However, given the widespread use of glyphosate‐based herbicides, residues of glyphosate and its major metabolite AMPA have been found in surface waters, soil (Huang, Pedersen, Fischer, White, & Young, ; Struger et al, ) and some plants such as legume, cereal, rice, wheat seed, canola seed and various types of animal fodder (Arregui et al, ; Cessna et al, ; Cessna, Darwent, Townley‐Smith, Harker, & Kirkland, ; Cetin, Sahan, Ulgen, & Sahin, ; Cuhra, ; FAO/WHO, ). Glyphosate is primarily absorbed through the skin, intestine and respiratory tract, and has been detected in many human urine samples, not only in those of farmers but also in those of the general public (Acquavella et al, ; Arbuckle, Lin, & Mery, ; Niemann, Sieke, Pfeil, & Solecki, ; Krüger et al, ).…”
Section: Introductionmentioning
confidence: 99%